The Role of Religion in Voters’ Preference During General Election 2014 in Central Java DI JAWA TENGAH - Arif Sofianto (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
Muslims are the largest part of Indonesian society, but in the history of elections,Islamic political parties have never won. The nationalist party tended to be a strongparty, whereas religion-based party tend to be a weak party. This study aims toanalyze how the influence of religion values on voting behavior during legislativeelections in the Central Java. This study was conducted in 10 electoral districts inCentral Java and it involved 400 respondents. This research used a qualitative and aquantitative method. The result depicted that religious values were used by voters asreference in assessing political figures whether they are good or bad, without lookingat the background of parties and ideologies. Voters are more influenced by rationaland pragmatic considerations than the leaders or religious organization.